AUTONOMY IN HIGHER EDUCATION FROM AFFILIATION TO SELF GOVERNING MANAGEMENT: AN INDIAN PERSPECTIVE - Yerande, Vitthal Laxmanrao (PEOPLE: International Journal of Social Sciences, 2018)
Many issues pertaining to autonomy of the higher educational institutions are discussed and emphasized throughout the universities and colleges in India. The University Grants Commission (UGC), National Assessment and Accreditation Council (NAAC) and government are spearheading this movement of ‘auto-nomination’ of higher education institutions. Here it is important to note that, the decline of quality in higher education in India underlines the importance of autonomy of the institutions. The adoption of affiliation system made the existing higher educational scenario mechanical and less useful in the era of globalization; consequently, the education system has become outdated and irrelevant in the present circumstances. The decline in the quality education motivated the researcher to think about means which can bring qualitative change in higher education. Autonomy in Higher Education is found as a ray of hope to reach the goal of quality education, for that the study started with the objectives of discussing present affiliation system and need of autonomy in higher education. The present paper has been prepared with the help of secondary data obtained from various book, journals, newspapers and e-sources. The empirical and descriptive method of research has been used for the paper. The researcher found that financially strong colleges should adopt autonomy and restructure the curricular according to local needs and the autonomous colleges should create their own infrastructure to produce skilled and well trained human resource to meet the modern needs. The study can further be extended in the areas of technological advancements in higher education as well as comparative study between two or more developing nations.